2021
DOI: 10.1002/jcla.23781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular genetic analysis of a Chinese family with hereditary elliptocytosis caused by a novel mutation in the EPB41 gene

Abstract: Background: Hereditary elliptocytosis (HE) is a heterogeneous red blood cell membrane disorder characterized by the presence of elliptocytes on a peripheral blood smear. Clinical manifestations of HE vary widely from asymptomatic carriers to patients with severe transfusion-dependent anemia. Most patients are asymptomatic or have mild anemia, which hinders diagnosis. The proband in this case had mild anemia and jaundice over a period of 4 years, the etiology of which was unclear. Hence, he was admitted to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The heterogenous SPTA1 IVS33-1G>A mutation was responsible for HE ( 15 ). Cao et al identified a heterozygous mutation 1294delA in exon 15 of the EPB41 gene using high-throughput sequencing and Sanger sequencing in members of a Chinese family ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The heterogenous SPTA1 IVS33-1G>A mutation was responsible for HE ( 15 ). Cao et al identified a heterozygous mutation 1294delA in exon 15 of the EPB41 gene using high-throughput sequencing and Sanger sequencing in members of a Chinese family ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…16 However, HE is also found in Europe, Mediterranean, Middle East, Japan, and India. 17 It is caused by mutations in α-spectrin, β-spectrin, and protein 4.1 which cause a defect in horizontal interactions of RBC cytoskeleton. The presence of elliptical shaped RBC is a morphological trait of HE.…”
mentioning
confidence: 99%